LINGUACULTURAL ANALYSIS OF METAPHORS IN THE WORKS OF ENGLISH AND KARAKALPAK WRITERS - Karjawbaev Orazali Esbosin uli (Journals Park Publishing, 2023)
We would like to mention here that the methods used by us in the process of learning activities are based on the consciouscomparative approach. This is based on the principle of awareness of linguistic phenomena in the period of learning and using, and on the principle of a comparative study of languages.
Keywords: research work, comparative languages, metaphors.